Political constraints on division of labor in development policy across countries: A proposal for a more viable coordination procedure at the EU level - Simon Hartmann (Austrian Foundation for Development Research (ÖFSE), 2011)
This paper discusses integral implementation problems of the aid harmonization process within the European Union (EU) which has pretty much failed to show up with convincing results yet. Therefore this paper looks on the origins of the problems EU donors struggle with. It has turned out that in the past, comparative advantage assessment has been avoided by most donors. Hence, it is argued here that it is more a barrier rather than viable approach to an effective implementation of Division of Labor (DoL) in development policy. Incentives from the arena of international politics are underlying constraints for this procedure and thus crucial to understanding the problems of implementation. It is also argued that the regulations currently in place obscure the real problems of too much aid proliferation and too little aid harmonization. Therefore it is important to bring back political dialogue to allow a widening of the discussion about the effectiveness of aid, which is has yet been dominated by a very narrow, technical approach. Understanding the political constraints is of major importance to understanding the problems of aid harmonization. As the technical challenges of the DoL have already been convincingly analyzed by the OECD, this paper analyzes the politics of aid harmonization and their contributions to the problems of the current EU approach, and finally suggests an alternative route. This paper argues that a more viable procedure must take the political conditions of aid into account and should therefore rather focus on the specialization rather than comparative advantage as an organizing principle for aid harmonization. – – Harmonisierung von Entwicklungspolitik ist eines der Hauptanliegen der Wirksamkeitsagenda der OECD. Dem stehen derzeit in erster Linie zwei fundamentale Probleme gegenüber: donor proliferation (eine ausufernde Anzahl an Geber pro Empfängerland) und aid fragmentation (eine große Anzahl von geringfügigen EZA-Engagements). Diese haben nachteilige Auswirkungen für die Entwicklungspolitik und deren Zielsetzungen. Eine Veränderung der aktuellen Praxis wollte die EU-Kommission durch einen "Verhaltenskodex für Komplementarität und Arbeitsteilung in der Entwicklungspolitik" im Jahr 2007 erwirken, dessen Ziel die Abstimmung der entwicklungspolitischen Strategien war. Später folgte der Operational Framework on Aid Effectiveness (operativer Rahmen zur Wirksamkeit der Entwicklungspolitik), der die Umsetzung der Harmonisierungsvorhaben regelte. ...
Keywords: 330; Entwicklungshilfe; Internationale Wirtschaftspolitik; Entwicklungshilfe; Europäische Integration; EU-Staaten